Monetary Fines in EU Mergers: In Need for More Regulation - Nora Memeti (Market and Competition Law Review)
Monetary fines represent an important instrument to address violations of Competition Law. The European Commission (EC) and the EU Courts have been primarily engaged in imposing fines in cases of breach of the first pillar, and have rarely dealt with cases of abuse based on the fining guidelines issued in accordance with Article 23(2) of Regulation 1/2003. Compared to the first two pillars, mergers have not received similar scholarly attention.1 2 Since 2017, the EC has expressed a growing interest in investigating and imposing significant fines to mergers and acquisitions in breach of procedural matters. Therefore this article addresses the application of Article 14 of the European Union Merger Regulation (EUMR) in imposing fines to mergers with European Union (EU) dimension. The EC decisions and EU Courts’ judgments related to fines on mergers in breach of procedural matters are discussed in four specific sections. The first section analyses article 14(1) of the EUMR, which empowers the EC to impose a fine of up to 1% of the total turnover in the preceding business year on undertakings for breach of procedural matters, including, among others, for providing incorrect or misleading information. This section will address the case of Facebook as the first case in which the EC imposed fines based on the new EUMR. In this case, although the undertakings mislead the EC, based on the offered cooperation, the Authority decided to reduce the fine. In addition, it is also important to address the legal basis applied by the EC in accepting the offered cooperation as a mitigating factor and whether this may develop into a guiding “precedent” in the future. The second section deals with five cases of violations of articles 4(1) and 7(1) EUMR related to fines prescribed in article 14(2) EUMR. With regards to four of them, judgments of EU Courts and decisions of the EC and National Competition Authority (NCA) are analysed. The fifth case, the one on Ernst and Young, provides for the first preliminary ruling on the notion of “gun-jumping”. The third section deals with Article 14(3) and the fining methods on mergers. By reviewing each of these five cases, it is important to address factors taken into consideration when imposing fines. An obvious deficiency is the absence of a legal basis, regardless of whether manifested in hard or soft law. Here it is relevant to inquire in what manner the EC imposes fines and why it occasionally mirrors the fining guidelines applicable to other pillars of EU Competition Law. The last point to be addressed is the one of policy and the need to balance EC discretional powers and relevant legal principles such as legal certainty, equal treatment, transparency, and consistency.3 The fourth section provides for concluding remarks.